Images et textes opératifs en design : énoncer, traduire les concepts, en et hors contexte - Éric Tortochot; Véronique Rey; Christina Romain (Appareil)
The images and texts that make up the designer’s forms of utterance are operational instruments for translating the emerging concepts within a design project. The translation of concepts is tested through a series of passages as needs evolve. These gestures or movements, which lead to representations and forms of utterance of the artifact’s desired shapes, are addressed to several interlocutors, whether or not they are design specialists. The documents are verbal and non-verbal information about the artefact, of a technical, conceptual, aesthetic or professional nature. Their “translations” are an assistance or an obstacle to the understanding of the shapes produced by the designers. In order to illustrate the specification at stake in a design activity, this study is based on an actual case involving uttered back-and-forth (reformulation, transmutation and transposition). This is a graphic design order for information sheets resulting in a failure, a stop of client order. Email interviews, audio interviews and graphic productions provide the corpus of analysis. The approach is multidisciplinary (cognitive and language sciences). It makes it possible to objectify the absence of shared representation, i.e. “enunciative translation”. This uttered translation does not take place because language interactions do not take into account either technical information or the specific terminological corpus of the company. The “translation gap” between the completed order and the graphic response is too large to allow the inter-comprehension system to function. The adaptation of the graphic writing to serve the client is not carried out. The failure of the order can therefore be explained by a lack of development of a shared representation (via design concepts) and thus illustrates the need for this uttered enunciative translation between the interlocutors.